WORKSHOP INOVASI PRODUK UNGGULAN DESA SENTUL HIJAB KAIN SUTERA: WORKSHOP INOVASI PRODUK UNGGULAN DESA SENTUL HIJAB KAIN SUTERA - Tirtoni, Feri; Supriyadi; Pramegista Dewanti Maharani (Universitas PGRI Adi Buana Surabaya, 2025)
This community service workshop explains the origins of development. This community service presents the results of a superior product innovation workshop in Sentul Village which focuses on developing hijabs from silk fabric. Background This community service is based on increasing consumer interest in local products and the need to increase added value to silk fabric products through design innovation and production processes. The aim of this community service is to develop innovative methods in the production of silk hijabs that can increase product competitiveness in an increasingly competitive market. The research method uses socialization and workshop methods. The results of this community service include the development of new silk hijab designs that combine traditional elements with a modern touch, as well as improvements in the production process to increase efficiency and quality. The conclusion of this community service emphasizes that product innovation is the key to increasing the competitiveness of local products, as well as highlighting the importance of cooperation between local industry players and the government in accelerating the innovation process to enter a wider market. These findings can make a positive contribution to the development of local creative industries, as well as increase understanding of the importance of innovation in maintaining and increasing the competitiveness of local products in the global market.